PERAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN SUPERVISI KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI INTRINSIK TERHADAP KINERJA GURU SMA KABUPATEN PATI - Agus Widhiyarso, 1252020025; Sunarto, Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine The Role of Transformational Leadership Style and Supervising Principal Moderating Effects of Intrinsic Motivation on the Performance of High School Teachers Kab.Pati. The study sample as many as 183 people. Purposive sampling technique uses proportional sampling. The data analysis in this study uses : Test Validity by factor analysis, reliability test by Cronbachs Alpha, Test models with Adjusted R2 and F-test, Hypothesis testing with the t test. The results showed that : 1) Intrinsic Motivation doesnât effect on teacher performance, 2) Transformational leadership style effect and relate positively significant on teacher performance, 3) Supervision of the principal effect and relate positively significant on the performance of teachers, 4) The transformational leadership style doesnât moderate the influence of intrinsic motivation on teacher performance, 5) Supervision of the principal doesnât moderate the influence of intrinsic motivation on teacher performance. The conclusion of this research, to improve the performance of SMA civil servant teachers in Kab.Pati can be done by using a transformational leadership style and accompanied by a supervising principal. Keywords : transformational leadership style, supervising principals, intrinsic motivation and performance.